Pengaruh Layanan Konseling Kelompok terhadap Kedisiplinan Belajar Siswa SMA Ali Maksum Yogyakarta - Haryati Haryati; Afifatuz Zakiyah; Erika Septianti Kusumaputri (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This study aims to determine the influence of group counseling services on the learning discipline of class X students of SMA Ali Maksum Yogyakarta. The population in this study was class X students of Ali Maksum High School who had low learning discipline. The sample in this study was 40 students. The sampling technique uses purposive sampling technique, which is the determination of samples based on predetermined characteristics, namely class X students of Ali Maksum High School Yogyakarta who have low learning discipline. Teknik data collection through Pre-Test and Post-Test. Pre-Test is carried out to collect data before treatment is carried out. The implementation was carried out using a shiva disciplinary questionnaire with a Likert scale. The result of this study is the positive influence of group counseling services on the learning discipline of class X students of Ali Maksum High School.